The ESC Textbook of Sports Cardiology (The European Society of Cardiology Series, 2019)
Sports and exercise have been intensely advocated as protective lifestyle measures which prevent or reduce the risk of severe health issues, including cardiovascular disease. More extreme forms of sports (for instance at high altitudes) have been identified as an important way of promoting cardiovascular adaptation, but have also been associated with adverse effects and even major cardiovascular events in predisposed individuals. Participating in more commonplace sports and exercise, such as football, may also increase a person's risk of cardiac events. This publication is timely in the light of a burgeoning number of clinical papers in the field.